2004
DOI: 10.1007/s11906-004-0083-8
|View full text |Cite
|
Sign up to set email alerts
|

The tissue renin-angiotensin-aldosterone system in diabetes mellitus

Abstract: Diabetes is associated with an inordinate burden of cardiovascular and renal disease, which is expected to accelerate during the next few decades. The relationship between the renin-angiotensin system (RAS) and diabetic macrovascular and microvascular disease is well established. The contribution of the tissue RAS in disease pathogenesis has recently been the focus of much interest, and has prompted investigators to explore the use of high-dose RAS inhibition with monotherapy or combination therapy to provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…Inhibition of the renin system with ACE-inhibitors or angiotensin receptor blockers (ARBs) is an attractive therapeutic approach for this patient group because increased tissue renin system activity may be a major factor in the development of organ damage in diabetes. 5,6 Indeed, clinical trials have shown that ACE-inhibitor or ARB treatment slows the progression of renal disease in patients with type 2 diabetes and hypertension. 7,8 ACE-inhibitors and ARBs inhibit negative feedback mechanisms, resulting in a reactive increase in plasma renin activity (PRA; the capacity of renin to convert angiotensinogen to angiotensin [Ang] I) that may lead to increased generation of Ang II.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of the renin system with ACE-inhibitors or angiotensin receptor blockers (ARBs) is an attractive therapeutic approach for this patient group because increased tissue renin system activity may be a major factor in the development of organ damage in diabetes. 5,6 Indeed, clinical trials have shown that ACE-inhibitor or ARB treatment slows the progression of renal disease in patients with type 2 diabetes and hypertension. 7,8 ACE-inhibitors and ARBs inhibit negative feedback mechanisms, resulting in a reactive increase in plasma renin activity (PRA; the capacity of renin to convert angiotensinogen to angiotensin [Ang] I) that may lead to increased generation of Ang II.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 In addition, animal studies have shown that ARBs enable endogenous angiotensin II to stimulate neuronal regeneration via activation of AT 2 receptors. 11 Although the relationship between the tissue RAS and diabetic macrovascular and microvascular disease is well established, 12 the effects of ARBs on cerebral metabolism and hemodynamics have not been fully investigated.…”
mentioning
confidence: 99%
“…Elevated endogenous AII is believed to cause organ damage (32). For example, Takai et al reported that although BP was not lowered, trandolapril reduced tissue ACE activity and prolonged survival in SHRSP (33).…”
Section: Discussionmentioning
confidence: 99%